2009
DOI: 10.1002/adsc.200900721
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active and Selective Semihydrogenation of Alkynes with the Palladium Nanoparticles‐Tetrabutylammonium Borohydride Catalyst System

Abstract: Palladium nanoparticles are prepared from palladium(II) acetate and 2 equivalents of potassium tert-butoxide in the presence of 4-octyne. The palladium nanoparticles-tetrabutylammonium borohydride system shows excellent catalytic activity and selectivity in the semihydrogenation of alkynes to the [(Z)-]alkenes. The hydrogenation of 4-octyne is conducted with the catalyst system at a substrate-to-palladium molar ratio of 10,000-200,000 under 8 atm of hydrogen to give (Z)-4-octene in > 99% yield. Isomerization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 45 publications
1
39
0
Order By: Relevance
“…214 In addition, differently shaped palladium nanocrystals with controlled size have been assayed in selective alkyne semi-hydrogenations, such as nanohexagons and nanospheres 215 or nanocubes 216 for the hydrogenation of 2-methyl-3-butyn-2-ol to the corresponding alkene, the nanocrystals shape becoming in important factor in the selectivity of the process. The reaction of PdCl 2 dispersed in TBAB with tri-n-butylamine at 120°C led to stable isolable PdNPs which have been dispersed in an ionic liquid or in methanol or used in solventless conditions for the cis-selective hydrogenation of 2-hexyne (2 bar of hydrogen and 20°C), the use of [bmim][BF 4 ] as ionic liquid allowing the recycle of the catalyst up to four times keeping the reaction rate.…”
Section: Scheme 68mentioning
confidence: 99%
“…214 In addition, differently shaped palladium nanocrystals with controlled size have been assayed in selective alkyne semi-hydrogenations, such as nanohexagons and nanospheres 215 or nanocubes 216 for the hydrogenation of 2-methyl-3-butyn-2-ol to the corresponding alkene, the nanocrystals shape becoming in important factor in the selectivity of the process. The reaction of PdCl 2 dispersed in TBAB with tri-n-butylamine at 120°C led to stable isolable PdNPs which have been dispersed in an ionic liquid or in methanol or used in solventless conditions for the cis-selective hydrogenation of 2-hexyne (2 bar of hydrogen and 20°C), the use of [bmim][BF 4 ] as ionic liquid allowing the recycle of the catalyst up to four times keeping the reaction rate.…”
Section: Scheme 68mentioning
confidence: 99%
“…These Pd NPs exhibited excellent catalytic activity in selective partial hydrogenation of alkynes and chemoselective hydrogenation of nitroarenes. 12,13 In the course of our study, we found that the Pd NPs 1b efficiently catalyze chemoselective hydrogenation of aryl and alkyl azides. Here, we would like to describe the features of the convenient functional group transformation.…”
Section: 11mentioning
confidence: 74%
“…12 Pd NPs 1 in DMF (10 mM) are homogeneously dispersed and have a shelf-life of more than a year at ambient temperature without aggregation. These Pd NPs exhibited excellent catalytic activity in selective partial hydrogenation of alkynes and chemoselective hydrogenation of nitroarenes.…”
Section: 11mentioning
confidence: 99%
“…Some disadvantages of the catalyst described originally by Lindlar led to an improvement of the processes. Thus, new catalyst systems, modifiers and additives have been envisioned for this problem of chemoselective hydrogenation [48][49][50][51][52][53][54][55][56][57][58]. Different variations and reagents were found capable of reducing the original catalytic reactivity of the Pd centers, resulting in a selective and partial hydrogenation of the employed alkyne [50].…”
Section: Lindlar-type Hydrogenation Of Diphenylacetylenementioning
confidence: 99%